Male description of Horcomutilla projectifrons (Cresson, 1902) Hymenoptera, Mutillidae) and the first host record for the genus - Lopez, Vinicius M.; Bartholomay, Pedro R.; Lima, Felipe V.o.; Silvestre, Rogerio (Zootaxa, 2019)
Velvet ants (Mutillidae) are solitary wasps whose larvae act as ectoparasitoids of encapsulated immatures of other insects, especially other solitary Hymenoptera (Luz et al. 2016). The natural history of most mutillids is unknown; for example, only 2–3% of the species have their hosts reported (Brothers 1989). Apidae species, however, are among the hymenopterans most commonly parasitized by velvet ants, with over 30 recorded cases in literature involving different genera of both host and parasite (Luz et al. 2016).